Pump Damage in the Hanshin Earthquake - Toshiyuki Osada (International Journal of Rotating Machinery)
There was a severe earthquake in the southern area ofHyogo prefecture in Japan on January 17, 1995. In this paper the damage to pump facilities caused by the earthquake, based on field investigation results in the Hanshin (Osaka–Kobe) area is reported. In particular a lot of damage was reported in the pumping facilities for sewage or drainage of storm sewage. This paper also presents recommendations for aseismic design of pump facilities based on the results of the survey.